THE EFFECT OF PRICE DISCOUNT, HEDONIC SHOPPING MOTIVATION, AND SHOPPING LIFESTYLE ON IMPULSE BUYING OF FASHION PRODUCTS ON SHOPEE LIVE (CASE STUDY OF STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITAS MALIKUSSALEH ) - Adnan; Dara; Naufal Bachri; T.Edyansyah (RADJA PUBLIKA, 2024)
The purpose of this research is to determine and analyze the influence of price discounts, hedonic shopping motivation and shopping lifestyle on fashion products on Shopee Live. The population in this study were active students at the Faculty of Economics and Business, Malikussaleh University. The sample in this study were students who had impulse bought fashion products on Shopee Live. The number of respondents used in this research was 100 people. Primary data in this research was taken by means of a questionnaire or distributing questionnaires, and secondary data was obtained from journals and internet media. The data analysis technique used is the multiple linear regression analysis method, classical assumption testing, instrument testing (validity and reliability), hypothesis testing and coefficient of determination using the SPSS version 26.0 program. This type of research is quantitative research. The results of this research show that simultaneously price discounts, hedonic shopping motivation and shopping lifestyle have a positive and significant effect on fashion products on Shopee Live among students at the Faculty of Economics and Business, Malikussaleh University. In particular, each variable, namely price discount, hedonic shopping motivation and shopping lifestyle, has a positive and significant effect on impulse buying of fashion products on Shopee Live. Hedonic shopping motivation is the most dominant variable influencing impulse buying of fashion products on Shopee Live at the Faculty of Economics and Business, Malikussaleh University. The adjusted R square value of 0.623 obtained by the dependent variable can be explained by the independent variables, namely price discount, hedonic shopping motivation and shopping lifestyle, amounting to 62.3%, while the remaining 37.7% can be explained by other variables which were not examined by this researcher.